57.8k views
5 votes
−1⋅f(−9)+7⋅g(6) please

2 Answers

1 vote

Answer:

multiply everything in the bracket e.g f multiplied by -g + 7.g multiplied by 6 =-1 -9g+7g6 but what is he full question? hun

User Pramit
by
5.3k points
5 votes

The solution of the expression is 38

How to solve the expression

The expression −1 * f(−9) + 7⋅* g(6) is solved using the information from the graph, to get the values, then applying PEMDAS to perform the calculation

From the grave we have that

f(−9) = 4 and

g(6) = 6

plugging in these values

= −1 * f(−9) + 7⋅* g(6)

= −1 * 4 + 7⋅* 6

= -4 + 42

= 38

−1⋅f(−9)+7⋅g(6) please-example-1
User Nouman Zaka
by
5.3k points